Crime Fiction Reloaded - Zsámba, Renáta (Hungarian Journal of English and American Studies, 2020)
Book review:Edwards, Martin. The Golden Age of Murder. London: Harper Collins, 2015. 528 pages. ISBN 0008105960. Hb. £16.59.